AN ANALYSIS OF COLD STORE BY CFD SIMULATION - Praneeth H R,PG Student; Dr. B. Sadashive Gowda (International Journal of Innovations in Engineering Research and Technology, 2021)
This paper deals with the numerical analysis of 3d model ofacold storeof dimensions 4.5 m (L) x 3.3 m (W) x 2.5 m (H),which isdeveloped to study the effects of design parameters on flow and temperature fields within the cold store. The variation in number of inlets, position of inletsand stacking methodology affectflow and temperature fields within the cold store. Results of CFD simulation indicated the optimum position of the inlets, number of inletsand stacking methodologyrequiredto have uniform flow and temperature field within the cold store. It also proved that CFD is a convenienttool for designing and optimizing the flow field in the cold store.